Explaining the Original Understanding of Lopez to the Framers: Or, The Framers Spoke Like Us, Didn't They? - Conrad J. Weiler Jr. (Washington University Journal of Law & Policy, 2004)
An important part of the Court’s rationale in Lopez, and other “new federalism” decisions, is a sense that they are returning to the original meaning of the Constitution. We are aware that there may be differences between the Framers’ intent and the original understanding of the meaning of the Constitution when it was adopted. The discussion here will not enter into the debate over the methods and propriety of originalism, nor is it necessary. What we do here is to focus narrowly on one aspect of Lopez’s connection with the Framing era, which is to consider whether there is semantic continuity between key words of the Lopez holding and words the Framers and Americans of their day would have used; or, in other words, to perform a kind of reverse textualism and see how the Framers would have understood Lopez. After examining the meaning of key words in the Lopez holding and what they meant in the eighteenth century, we conclude not only that neither the Framers nor any American of their day would have understood Lopezto have anything like the meaning intended by the Lopez majority, but because of changed meanings of language the Framers would likely have violently rejected the literal holding of Lopez. We conclude by considering what this repugnancy between the language of Lopez and the language of the Framers means for the originalism of Lopez, its overall intelligibility, and the regulation of commerce.
Keywords: Interstate commerce clause (Constitutional law); Federal government; Textualism (Legal interpretation); Originalism (Constitutional interpretation); United States v. Lopez (1995)